齿轮接触疲劳极限应力快速测定法的应用 - 李红梅; 王铁; 张瑞亮 (Jixie chuandong)
The gear pitting damage is the main failure form of closed gear transmission.Therefore,the tooth surface pitting resistance capability and the accuracy of tooth surface contact fatigue strength calculation are directly related to the quality and life of gear.The rapid test method,called Locati,is applied to gain the estimated value of fatigue limit stress of the gear,and MATLAB is applied to carry on data processing and get gear fatigue life curves and the cumulative damage curve.